2019
DOI: 10.1371/journal.pone.0220124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nighttime procedures on outcomes after liver transplantation

Abstract: Background Sleep deprivation is a well-known risk factor for the performance of medical professionals. Solid organ transplantation (especially orthotopic liver transplantation (oLT)) appears to be vulnerable since it combines technically challenging operative procedures with an often unpredictable start time, frequently during the night. Aim of this study was to analyze whether night time oLT has an impact on one-year graft and patient survival. Material and methods Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…In addition, it was not analyzed whether TIVAP implantation was routinely scheduled or conduced as an urgent procedure to allow for rapid start of chemotherapy in critical cases. Although this might be a minor bias, time of operation has been proven to affect outcomes of surgical procedures [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was not analyzed whether TIVAP implantation was routinely scheduled or conduced as an urgent procedure to allow for rapid start of chemotherapy in critical cases. Although this might be a minor bias, time of operation has been proven to affect outcomes of surgical procedures [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Similarly, surgery during the daytime had fewer complications than at nighttime. 20,21 Workload and fatigue may be major contributors to these outcomes. China is a populous country and has the largest number of gastric cancer patients worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, many transplantations occur during night-time hours [20]. Although studies have shown that patient outcomes are not impacted by night-time transplants, over time, the combination of night-time operating and a busy transplantation service can lead to transplant team burnout and potentially a lack of personnel available for call coverage [20][21][22][23][24]. The introduction of NMP has enabled a shift of transplantation from night-time to daytime hours, as NMP can be run overnight [7,25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential clinical benefits of NMP, the surgical teams may also benefit. Traditionally, many transplantations occur during night-time hours [ 20 ]. Although studies have shown that patient outcomes are not impacted by night-time transplants, over time, the combination of night-time operating and a busy transplantation service can lead to transplant team burnout and potentially a lack of personnel available for call coverage [ 20 24 ].…”
Section: Discussionmentioning
confidence: 99%